Bodily communions: An eschatological proposal for addressing the Christian body problem - MacDougall, Scott (Dialog, 2018)
This article is a programmatic proposal for providing a theological and existential (experiential and practical) framework for addressing the problem of the body in Christianity, specifically by examining the body against its eschatological horizon. It outlines the character of the problem, specifies an eschatological approach for addressing it, and begins to unfold a number of topics regarding embodiment that have new salience when apprehended in eschatological terms. It concludes by providing a preliminary agenda for carrying such a project forward.